Peningkatan Layanan dalam Keterbatasan Sumber Daya Manusia (SDM) - Fuad Zein, Zakiyul (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper discusses the gap between the number of students and the number of academic staff at UIN Sayyid Ali Rahmatullah Tulungagung. Excellent academic service must be supported by adequate quality and quantity of academic human resources (HR). As a Public Service University, UIN Sayyid Ali Rahmatullah Tulungagung provides both academic and non-academic services. To provide these services, adequate human resources are needed. Academic staff spearhead services to the students and society in general. The author tries to find a solution to the rapid increase of the number of students which is not followed by the increase of the number of academic human resources. This condition causes the ratio of the number of students to the available academic staff to be less than ideal. It has an impact on the quality of the services provided. Fast and friendly services are hard to achieve. Using descriptive qualitative methods, the author analyzes the sources of problems and looks for solutions to these problems. As a result, the author recommends: 1) the university leader limit the selection quota for new student admissions; 2) the university leader build an application system that is integrated into one web, Android, and IOS-based database system; 3) the university leader involves other parties in providing certain services; and 4) the university leader uses the Management Cooperation (MC) method in managing the non-academic business so that available human resources can focus more on academic services as the core business of PSA of UIN Sayyid Ali Rahmatullah Tulungagung.